2021
DOI: 10.1177/03635465211056082
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport in Athletes With Borderline Hip Dysplasia After Hip Arthroscopy for Femoroacetabular Impingement Syndrome

Abstract: Background: Data on outcomes in patients with borderline hip dysplasia (BHD) who undergo hip arthroscopy remain limited, particularly in regard to return to sport (RTS). Purpose: To evaluate outcomes in patients with BHD and their ability to RTS after hip arthroscopy for treatment of femoroacetabular impingement syndrome (FAIS). Study Design: Case series; Level of evidence, 4. Methods: Consecutive patients with self-reported athletic activity and radiographic evidence of BHD, characterized by a lateral femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Although high return-to-sports rates have been reported after hip arthroscopic surgery in patients with BHD, 2,13,24 to our knowledge, no study to date has reported on return to sports and activity levels in patients with BHD after PAO. However, this information is essential to be able to counsel active patients in the choice of a surgical management strategy for BHD, as hip arthroscopic surgery and PAO are procedures of different magnitudes, which presumably could have implications in return to sports.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although high return-to-sports rates have been reported after hip arthroscopic surgery in patients with BHD, 2,13,24 to our knowledge, no study to date has reported on return to sports and activity levels in patients with BHD after PAO. However, this information is essential to be able to counsel active patients in the choice of a surgical management strategy for BHD, as hip arthroscopic surgery and PAO are procedures of different magnitudes, which presumably could have implications in return to sports.…”
mentioning
confidence: 83%
“…15,21 At the time of indication, regardless of the surgical approach chosen, patients are usually young and active with high functional demands. Those who participate in sports want to resume and maintain sports activities after surgery, 2,6,13,18,[23][24][25] and the ability to do so plays an important role in the choice of a treatment method.…”
mentioning
confidence: 99%
“…Patients with flexibility sport participation at the recreational, high school, collegiate, and professional level were deemed athletes and were eligible for study inclusion in accordance with previous literature. 1,17,33,47 Exclusion criteria were patients undergoing revision hip arthroscopy, pincer deformity (defined as an LCEA >40° 29 ), severe dysplasia (LCEA <18°), patients with a connective tissue disorder (eg, Ehlers-Danlos syndrome), patients undergoing a concomitant hip procedure (eg, gluteus medius/minimus repair), patients undergoing a staged periacetabular osteotomy (PAO), Tönnis grade >1 osteoarthritis, and those with a developmental hip disorder (eg, Legg-Calvé-Perthes disease or slipped capital femoral epiphysis). The included patients were compared with a propensity score–matched group of patients with normal coverage (LCEA ≥25° and <40°) who underwent primary hip arthroscopy for FAIS within the same time frame.…”
Section: Methodsmentioning
confidence: 99%
“…In cases in which cam impingement was present (defined as an alpha angle >50° on preoperative AP pelvic or 90° Dunn lateral radiograph and intraoperative evidence of femoroacetabular impingement on dynamic examination), femoroplasty was performed under direct arthroscopic and fluoroscopic guidance. 1,43 In cases of inadequate femoral neck exposure, the interportal capsulotomy was extended vertically to create a T-type capsulotomy. After femoroplasty, dynamic examination was performed to ensure joint congruency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation